Electronic Transitions in Conformationally Controlled Peralkylated Hexasilanes. Issue 19 (9th August 2016) - Kanazawa, Yuki; Tsuji, Hayato; Ehara, Masahiro; Fukuda, Ryoichi; Casher, Deborah L.; Tamao, Kohei; Nakatsuji, Hiroshi; Michl, Josef
Abstract: The photophysical properties of oligosilanes show unique conformational dependence due to σ‐electron delocalization. The excited states of the SAS, AAS, and AEA conformations of peralkylated n ‐hexasilanes, in which the SiSiSiSi dihedral angles are controlled into a syn (S), anti (A), or eclipsed (E) conformation, were investigated by using UV absorption, magnetic circular dichroism (MCD), and linear dichroism spectroscopy. Simultaneous Gaussian fitting of all three spectra identified a minimal set of transitions and the wavenumbers, oscillator strengths, and MCD B terms in all three compounds. The results compare well with those obtained by using the symmetry‐adapted‐cluster configuration interaction method and almost as well with those obtained by time‐dependent density functional theory with the PBE0 functional. The conformational dependence of the transition energies and other properties of free‐chain permethylated n ‐hexasilane, n ‐Si6 Me14, was also examined as a function of dihedral angles, and the striking effects found were attributed to avoided crossings between configurations of σσ* and σπ* character. Abstract : Simultaneous fitting of UV, magnetic circular dichroism (MCD), and linear dichroism (LD) spectra with Gaussians permits individual transitions in a hexasilane to be discerned and compared with symmetry‐adapted‐cluster configuration interaction (SAC‐CI) calculations, which account for their dramatic conformational dependence.